What multimodal data can tell us about the students' regulation of their learning process?. (April 2021) - Järvelä, Sanna; Malmberg, Jonna; Haataja, Eetu; Sobocinski, Marta; Kirschner, Paul A.
Highlights: New data-capturing devices allow researchers trace a range of cognitive and noncognitive processes. We discuss and demonstrate how by data triangulating it is possible to study a number of features of regulated learning. It is concluded that multimodal data can indicate critical features of regulated learning in collaboration.